DEVELOPMENT OF TRILINGUAL ILLUSTRATED DICTIONARY POP-UP MEDIA IN DEVELOPING LANGUAGE SKILLS IN CHILDREN AGED 5-6 YEARS AT RA ISLAMIYAH KABAT, BANYUWANGI - Indana Zulfa; Riris Wahyuningsih; Fitriatul Masruroh (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Language development in children is the ability to express language verbally, both to know pictures and to communicate. Based on the results of the observations by researchers, it is known that students at Islamiyah Islamic Kindergarten use regional languages (Osing) as a language to interact in daily life. In contrast, students interact using Indonesian in the teaching and learning process. Islamiyah Islamic Kindergarten also introduces Arabic to students to increase their knowledge of foreign languages. Using the local language (Osing) in this media aimed to make it easier for students to know the objects around them. Indonesian is the language of instruction, so the media developed can be used widely, especially in Indonesia. Early childhood is a golden period of child development and growth, so it is very good to introduce foreign languages (Arabic) to children. Learning media can represent what the teacher cannot say through words, so the presence of learning media can concretize the abstractness of learning materials. This development research aimed to produce valid, effective, and practical multimedia-based learning media. This development research used the 4D model, which consists of four stages: define, design, develop, and disseminate. The research subjects were Islamiyah Islamic Kindergarten students in Bunder village, Kabat district. The results showed that the average value of validity was 3.6. The effectiveness of the media on student learning outcomes is 78.52. The validity of the media is obtained from the validator's assessment with a material validity value of 3.75% and media validity of 3.18%, which means the media is valid.